An annotated checklist of the Cladocera (Crustacea: Branchiopoda) from India - Chatterjee, Tapas; Kotov, Alexey A.; Damme3, Kay Van; Chandrasekhar, S. V.a.; Padhye, Sameer (Zootaxa, 2013)
Based on a revision of available literature on the Indian Cladocera (Crustacea: Branchiopoda), we present an updated checklist, with taxonomical updates and comments for all taxa recorded since the start of research of this group in the country since 1860. We have listed a total of 137 valid taxa, of which most records belong to species groups that need revision worldwide. The situation in Indian Cladocera taxonomy is, at present, insufficient for realistic conclusions on biodiversity, ecology and biogeography. We list suggestions for an improvement of the current situation.